PENGARUH BIAYA OPERASIONAL, DANA PIHAK KETIGA DAN NON PERFORMING FINANCE TERHADAP PERTUMBUHAN LABA PADA PERBANKAN SYARIAH DI INDONESIA - Cut Marliana TA; Meutia Fitri (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
This study aimed to examine the effect of operational cost, third parties fund and non performing finance to income growth.  The data used in this research is secondary data. The sample was taken by purposive sampling method and the number of samples obtained were 44 Islamic banking companies registered in Bank Indonesia from 2011-2014. The analysis technique used is multiple linear regression using SPSS 22.This study using operational cost, third parties fun and non performing finance as independent variable and income growth as the dependent variable. The results of this study indicate that the simultaneous testing (F test), variable operational cost, third parties fundm and non performing finance  to income growth. In the partial test (t test), variable operational cost, third parties fund, and non performing finance has an effect on income growth. Keyword : Income growth, operational cost, third parties fundm and non performing finance.